1986
DOI: 10.1042/cs0710151
|View full text |Cite
|
Sign up to set email alerts
|

The plasma release of atrial natriuretic peptide in man

Abstract: We studied plasma atrial natriuretic peptide (ANP) concentrations in seven normal subjects after the acute intravenous infusion of sodium chloride/potassium chloride solution (saline). Three separate infusions of 6, 12 and 18 ml of saline/kg body weight each significantly increased the circulating concentration of ANP without changes of plasma osmolality or electrolyte concentrations. The mean maximal rise of the plasma ANP concentration after the three saline infusions was significantly correlated (r = 0.74, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(49 citation statements)
references
References 0 publications
7
41
1
Order By: Relevance
“…Based on the finding that significant changes in atrial pressures achieved by the low infusion rate of phenylephrine were not accompanied by an increase in irANF, we would postulate that the increased secretion of ANF has a lag period after a pressure increase of at least 4 minutes and perhaps as much as 15 minutes. Our studies with hemodynamically monitored rapid saline infusions suggest a 2-to 15-minute lag period, 10 and Anderson et al 23 reported a 10-to 30-minute delay using a similar protocol.…”
mentioning
confidence: 92%
“…Based on the finding that significant changes in atrial pressures achieved by the low infusion rate of phenylephrine were not accompanied by an increase in irANF, we would postulate that the increased secretion of ANF has a lag period after a pressure increase of at least 4 minutes and perhaps as much as 15 minutes. Our studies with hemodynamically monitored rapid saline infusions suggest a 2-to 15-minute lag period, 10 and Anderson et al 23 reported a 10-to 30-minute delay using a similar protocol.…”
mentioning
confidence: 92%
“…ANP is released into the circulation after atrial distension. 9,10 Plasma ANP is considered a prognostic marker for acute heart failure, risk of cardiovascular events, and death. 11,12 Previous studies of ANP in maternal circulation in pregnancy are controversial, with reports of increased, [13][14][15][16] as well as similar, [17][18][19] circulating ANP concentrations in preeclampsia compared with normotensive pregnancy.…”
mentioning
confidence: 99%
“…Mean venous plasma IR-ANP concentration in resting adult subjects, consuming a normal diet, range from approximately 5 to 20 pmol/l (1 5-60 pg/ml) according to most published methods (Arendt et al, 1985;Yamaji et al, 1985b;Anderson et a[., 1986d;Weidmann et al, 1986a;Yandle et al, 1986b). Plasma levels may be higher in the elderly (Ohashi et al, 1986) but the effect of age and sex requires further study.…”
Section: Normal Subjectsmentioning
confidence: 99%
“…Since the metabolic clearance rate of IR-ANP is unaffected by major variations in sodium intake (Cuneo et al, 1986), these changes in plasma IR-ANP levels must be due to alterations in cardiac secretion of the peptide. Other manoeuvres causing central blood volume expansion such as intravenous saline loads (Sagnella et al, 1985;Yamaji et a!., 1985b;Anderson et al, 1986d) head out water immersion (Epstein et al, 1986) and head down tilting (Hodsman et al, 1985) also increase plasma IR-ANP. Presumably for the same reasons, plasma levels increase when subjects change posture from erect to supine position .…”
Section: Normal Subjectsmentioning
confidence: 99%